A case study of enhanced clinical care enabled by Aboriginal health research: the Hearing, EAr health and Language Services (HEALS) project. (23rd October 2016) - Young, Christian; Gunasekera, Hasantha; Kong, Kelvin; Purcell, Alison; Muthayya, Sumithra; Vincent, Frank; Wright, Darryl; Gordon, Raylene; Bell, Jennifer; Gillor, Guy; Booker, Julie; Fernando, Peter; et al.
Abstract: Objective : To describe and evaluate Hearing EAr health and Language Services (HEALS), a New South Wales (NSW) health initiative implemented in 2013 and 2014 as a model for enhanced clinical services arising from Aboriginal health research. Methods : A case‐study involving a mixed‐methods evaluation of the origins and outcomes of HEALS, a collaboration among five NSW Aboriginal Community Controlled Health Services (ACCHS), the Sydney Children's Hospitals Network, NSW Health, the Aboriginal Health and Medical Research Council, and local service providers. Service delivery data was collected fortnightly; semi‐structured interviews were conducted with healthcare providers and caregivers of children who participated in HEALS. Results : To circumvent health service barriers, HEALS used relationships established through the Study of Environment on Aboriginal Resilience and Child Health (SEARCH) to form a specialist healthcare network. HEALS employed dedicated staff and provided a Memorandum of Understanding (detailing mutual goals and responsibilities) for each ACCHS. Despite very tight timeframes, HEALS provided services for 653 Aboriginal children, including 5, 822 speech‐language pathology sessions and 219 Ear, Nose and Throat procedures. Four themes reflecting the perceived impact of HEALS were identified: valued clinical outcomes, raising community awareness, developing relationships/networks and augmented service delivery. Conclusions : HEALS delivered rapid and effective specialist healthcare services through an existing research collaboration with five ACCHS, cooperation from local health service providers, and effective community engagement. Implications for Public Health : HEALS serves as a framework for targeted, enhanced healthcare that benefits Aboriginal communities by encapsulating the 'no research without service' philosophy.